2002
DOI: 10.1080/136518202760378470
|View full text |Cite
|
Sign up to set email alerts
|

Bloodless hepatectomy technique

Abstract: Liver resection assisted by RF energy is feasible and safe. This technique could offer a new method for 'transfusion-free' resection without the need for sutures, ties, staples, tissue glue or admission to the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 9 publications
0
36
0
2
Order By: Relevance
“…This ensures occlusion of blood vessels and bile ducts of the line section, sealing also small lymphatic channels of the bloody face. The absence of biliary fistula associated with low levels of transoperative bleeding and postoperative drainage, seal the latter point of view, as well as the findings of other authors who use the RF for liver resections 13,14,22,25 . In the vast majority of hepatectomies aminotransferase elevations are described on a temporary basis, returning to normal levels by the end of a few days, a fact observed in these cases.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…This ensures occlusion of blood vessels and bile ducts of the line section, sealing also small lymphatic channels of the bloody face. The absence of biliary fistula associated with low levels of transoperative bleeding and postoperative drainage, seal the latter point of view, as well as the findings of other authors who use the RF for liver resections 13,14,22,25 . In the vast majority of hepatectomies aminotransferase elevations are described on a temporary basis, returning to normal levels by the end of a few days, a fact observed in these cases.…”
Section: Discussionmentioning
confidence: 79%
“…The temperature control of the needle prevents there early clotting cells around it, slowing the increase in tissue resistance, and allowing more uniform and extensive necrosis of the region. These authors 13,14,22,25 have shown that this distortion occurs in a cell radius of 0.5 cm around the needle, producing uniform and bloodless tissue mass. In the case of a monopolar system, the grounding plate is mandatory, and the risk of burns occur in front of the large discharge of energy, are not negligible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations